2018
DOI: 10.3174/ajnr.a5903
|View full text |Cite
|
Sign up to set email alerts
|

MRI Evidence of Altered Callosal Sodium in Mild Traumatic Brain Injury

Abstract: BACKGROUND AND PURPOSE: Mild traumatic brain injury is a leading cause of death and disability worldwide with 42 million cases reported annually, increasing the need to understand the underlying pathophysiology because this could help guide the development of targeted therapy. White matter, particularly the corpus callosum, is susceptible to injury. Animal models suggest stretch-induced mechanoporation of the axonal membrane resulting in ionic shifts and altered sodium ion distribution. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For TSC, we consider the only prior report of 23 Na MRI in TBI, a pilot study in 11 patients of 3 CC ROIs. 65 Compared to controls, patients had high TSC (genu), statistical trend for low TSC (splenium) and no findings (body). In our study, these regions showed unidirectional effect sizes for lower TSC in patients, without statistical effects.…”
Section: Discussionmentioning
confidence: 92%
“…For TSC, we consider the only prior report of 23 Na MRI in TBI, a pilot study in 11 patients of 3 CC ROIs. 65 Compared to controls, patients had high TSC (genu), statistical trend for low TSC (splenium) and no findings (body). In our study, these regions showed unidirectional effect sizes for lower TSC in patients, without statistical effects.…”
Section: Discussionmentioning
confidence: 92%
“…The corpus callosum was also included as commonly implicated in mTBI. 37 , 38 , 39 , 40 Region of interest volume (normalized for total intracranial volume), fractional anisotropy, or mean diffusivity were the y variables; group (patient vs control), age, and sex, the covariates; and scanner, a random intercept.…”
Section: Methodsmentioning
confidence: 99%